Insights into the differences related to the resistance mechanisms to the highly toxic fruit Hippomane mancinella (Malpighiales: Euphorbiaceae) between the larvae of the sister species Anastrepha acris and Anastrepha ludens (Diptera: Tephritidae) through comparative transcriptomics - García-Saldaña, Essicka A.; Cerqueda-García, Daniel; Ibarra-Laclette, Enrique; Aluja, Martín (Frontiers in Physiology, 2024)
The Manchineel, Hippomane mancinella ("Death Apple Tree") is one of the most toxic fruits worldwide and nevertheless is the host plant of the monophagous fruit fly species Anastrepha acris (Diptera: Tephritidae). Here we aimed at elucidating the detoxification mechanisms in larvae of A. acris reared on a diet enriched with the toxic fruit (6% lyophilizate) through comparative transcriptomics. We compared the performance of A. acris larvae with that of the sister species A. ludens, a highly polyphagous pest species that is unable to infest H. mancinella in nature. The transcriptional alterations in A. ludens were significantly greater than in A. acris. We mainly found two resistance mechanisms in both species: structural, activating cuticle protein biosynthesis (chitinbinding proteins likely reducing permeability to toxic compounds in the intestine), and metabolic, triggering biosynthesis of serine proteases and xenobiotic metabolism activation by glutathione-Stransferases and cytochrome P450 oxidoreductase. Some cuticle proteins and serine proteases were not orthologous between both species, suggesting that in A. acris, a structural resistance mechanism has been selected allowing specialization to the highly toxic host plant. Our results represent a nice example of how two phylogenetically close species diverged over recent evolutionary time related to resistance mechanisms to plant secondary metabolites.